2017
DOI: 10.1002/biot.201700248
|View full text |Cite
|
Sign up to set email alerts
|

A Strong Hybrid Fatty Acid Inducible Transcriptional Sensor Built From Yarrowia lipolytica Upstream Activating and Regulatory Sequences

Abstract: The engineering of Yarrowia lipolytica to accumulate lipids with high titers and productivities has been enabled with a handful of constitutive promoters for pathway engineering. However, the development of promoters that are both strong and lipid responsive could greatly benefit the bioproduction efficiency of lipid-derived oleochemicals in oleaginous yeast. In this study, a fatty acid regulated hybrid promoter for use in Y. lipolytica is engineered. A 200 bp upstream regulatory sequence in the peroxisomal ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…While the use of mannose as a carbon source has received limited attention, the role of mannose in glycoprotein biogenesis has been well studied ( Ezekowitz et al, 1990 ; Chiba et al, 1998 ; Hamilton et al, 2003 ; Zhu et al, 2009 ; Tiels et al, 2012 ). More recently, Y. lipolytica has been explored as a host for the production of therapeutic mannoproteins due to its efficient heterologous protein secretory capabilities and the growing set of genetic tools available, such as a suite of promoters and terminators ( Thevenieau et al, 2009 ; Blazeck et al, 2011 , 2013 ; Curran et al, 2015 ; Shabbir Hussain et al, 2016 , 2017 ), pooled promoters ( Dulermo et al, 2017 ), secretion markers ( Nicaud et al, 2002 ; Madzak et al, 2004 ), Golden Gate assembly ( Celińska et al, 2017 ), and CRISPR systems ( Gao S. et al, 2016 ; Schwartz et al, 2016 , 2017b ). Mannosylphosphorylated N -glycans are a precursor to produce mannose-6-phosphate containing glycoproteins.…”
Section: Hexose Substratesmentioning
confidence: 99%
See 1 more Smart Citation
“…While the use of mannose as a carbon source has received limited attention, the role of mannose in glycoprotein biogenesis has been well studied ( Ezekowitz et al, 1990 ; Chiba et al, 1998 ; Hamilton et al, 2003 ; Zhu et al, 2009 ; Tiels et al, 2012 ). More recently, Y. lipolytica has been explored as a host for the production of therapeutic mannoproteins due to its efficient heterologous protein secretory capabilities and the growing set of genetic tools available, such as a suite of promoters and terminators ( Thevenieau et al, 2009 ; Blazeck et al, 2011 , 2013 ; Curran et al, 2015 ; Shabbir Hussain et al, 2016 , 2017 ), pooled promoters ( Dulermo et al, 2017 ), secretion markers ( Nicaud et al, 2002 ; Madzak et al, 2004 ), Golden Gate assembly ( Celińska et al, 2017 ), and CRISPR systems ( Gao S. et al, 2016 ; Schwartz et al, 2016 , 2017b ). Mannosylphosphorylated N -glycans are a precursor to produce mannose-6-phosphate containing glycoproteins.…”
Section: Hexose Substratesmentioning
confidence: 99%
“…The fatty acids/acyl-CoAs that enter the peroxisome can then be degraded by the well-studied β-oxidation cycle. Recent work from our group reveals synergistic effects of glycerol and fatty acid mixtures on the expression of β-oxidation gene, POX2 ( Shabbir Hussain et al, 2017 ). Alternatively, the fatty acyl-CoA can enter the endoplasmic reticulum for incorporation into cellular lipids or TAGs ( Figure 4 ).…”
Section: Lipidsmentioning
confidence: 99%
“…Surprisingly, this study showed that natural yeast promoters could be considered as "enhancer-limited" and that transcription factor availability did not constitute a limiting factor for expression level. Besides UAS1XPR2, other enhancer elements have been made available as building bricks for the design of new recombinant promoters, notably the constitutive UASTEF [204], the erythritol/erythrulose-inducible UAS1EYK1 [200] and the fatty acid-inducible UASPOX2 [205]. This latter enhancer element was used in the design of a pPOX2-derived promoter with an unprecedented 48-fold induction level that could be used not only for metabolic engineering but also as a fatty acid biosensor [205].…”
Section: Natural Y Lipolytica Promoters and Promoter Engineeringmentioning
confidence: 99%
“…Besides UAS1XPR2, other enhancer elements have been made available as building bricks for the design of new recombinant promoters, notably the constitutive UASTEF [204], the erythritol/erythrulose-inducible UAS1EYK1 [200] and the fatty acid-inducible UASPOX2 [205]. This latter enhancer element was used in the design of a pPOX2-derived promoter with an unprecedented 48-fold induction level that could be used not only for metabolic engineering but also as a fatty acid biosensor [205]. New strong inducible recombinant promoters were derived from pEYK1 by tandem addition of multiple UAS1XPR2 or UAS1EYK1 enhancers [200].…”
Section: Natural Y Lipolytica Promoters and Promoter Engineeringmentioning
confidence: 99%
“…Fundamentals are always driving technological innovations. Blenner and his coworkers identified a short (200 bp) upstream regulatory sequence in the peroxisomal acyl CoA oxidase 2 (POX2) promoter in the oleaginous yeast Yarrowia lipolytica for engineering to more efficiently induce the expression of genes related to glucose metabolism and the biosynthesis of lipids, providing a useful tool for developing robust strains . Prof. Mattheos Koffas and his coworkers engineered E. coli to produce recombinant chondroitinase ACII and characterized its enzymology properties with an expectation of providing critical enzyme for the glycobiology research …”
mentioning
confidence: 99%